2015
DOI: 10.1590/01000683rbcs20140324
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Mineralization in Soil Combining Sewage Sludge and Straw

Abstract: The combined incorporation of sewage sludge (SS) and oat straw (OS) to the soil can increase straw carbon mineralization and microbial nitrogen immobilization. This hypothesis was tested in two laboratory experiments, in which SS was incorporated in the soil with and without OS. One treatment in which only straw was incorporated and a control with only soil were also evaluated. The release of CO 2 and mineral N in the soil after organic material incorporation was evaluated for 110 days. The cumulative C minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…For fertilizer inputs, Chantigny, Rochette, Angers (2001) found a strong interaction between C-rich barley straw residues and N-rich pig slurry when simultaneously incorporated into the soil, with the pig slurry stimulating the mineralization of straw-C. Conversely, Aita, Recous, Cargnin, da Luz, and Giacomini (2012) found the same proportion of straw-C mineralized when the straw was incorporated into the soil alone or with pig slurry. Giacomini et al (2015) also found that C mineralization was similar whether oat straw was incorporated into the soil alone or with sewage sludge. Therefore, the pattern of interaction between organic fertilizers and crop residues added together to a soil is unclear.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…For fertilizer inputs, Chantigny, Rochette, Angers (2001) found a strong interaction between C-rich barley straw residues and N-rich pig slurry when simultaneously incorporated into the soil, with the pig slurry stimulating the mineralization of straw-C. Conversely, Aita, Recous, Cargnin, da Luz, and Giacomini (2012) found the same proportion of straw-C mineralized when the straw was incorporated into the soil alone or with pig slurry. Giacomini et al (2015) also found that C mineralization was similar whether oat straw was incorporated into the soil alone or with sewage sludge. Therefore, the pattern of interaction between organic fertilizers and crop residues added together to a soil is unclear.…”
Section: Introductionmentioning
confidence: 68%
“…Conversely, Aita, Recous, Cargnin, da Luz, and Giacomini () found the same proportion of straw‐C mineralized when the straw was incorporated into the soil alone or with pig slurry. Giacomini et al () also found that C mineralization was similar whether oat straw was incorporated into the soil alone or with sewage sludge. Therefore, the pattern of interaction between organic fertilizers and crop residues added together to a soil is unclear.…”
Section: Introductionmentioning
confidence: 87%
“…This value is much lower than those found here, which were 97.6% and 91.8% for the incorporated compost and the applied over the soil surface, respectively, at a dose equal to 13.3 Mg ha -1 . However, GIACOMINI et al (2015) obtained respectively 45,3% and about 60% of the MFTOC and MFON, after 110 days of the domestic sludge incubation in a sandy soil. PEREIRA et al (2015) found values of mineralization fractions of OOC and ON, for peach palm residue, of 93.5 and 95.3%, when it was incorporated into the soil; and 59.8 and 62.7%, when disposed on soil surface, respectively, for 102 days of monitoring.…”
Section: Resultsmentioning
confidence: 90%
“…The similar values between treatments are due to the low amounts of C in the composition of the biofertilizer, because of the release of CO 2 and CH 4 in the biodigestion process (Medeiros and Lopes, 2006), the low C:N ratio, which favors rapid mineralization of the organic matter added to the soil (Giacomini et al, 2015), and the environmental conditions of the semiarid region, which do not favor a high supply of plant biomass in the native forest area (Alencar et al, 2015). As previously mentioned, close to the application site, there is the effect of wetting and drying cycles, which contribute to the packing of particles, forming less porous intra-aggregate arrangements.…”
Section: Soil Air Permeabilitymentioning
confidence: 98%